Research development in Tehran Nursing and Midwifery School, 2004: an action research report - Nikbakht Nasrabadi A; Parsa Yekta Z; Barimnejad L (Tehran University of Medical Sciences, 2005)
Introduction: Continuous professional development is an essential component within many health care 'Learning Organizations'. This paper describes an initiation to develop a professional practice development framework for faculties in Tehran Nursing and Midwifery School. Materials and Methods: The project was undertaken within an action research methodology with four phases .The goal of the project was to improve research, provide competition, reinforce data management, identify priority of needs in nursing and midwifery, and in so doing, enhance knowledge of the development of health information resources. A multi-method approach to data collection was undertaken to capture the change process from different stakeholders' perceptions. Triangulation of the data was undertaken. Despite organizational constraints, leadership and peer support enabled the co-researchers to identify and initiate high quality research initiatives. The change process for the co-researchers included: enlightening personal journey, exploring the research-practice gap, enhancing personal and professional knowledge, evolving cultural change and collaborative working. Results: Descriptive analysis and evaluation method showed that the project was done effectively. Conclusion: A more flexible time-scale and long term funding are required to enable continuity for trust-wide projects undertaken in dynamic academic settings